Implementasi Tindak Pidana Ringan Dalam Kasus Penganiayaan (Studi Putusan Nomor : 178/Pid.B/ 2017/ PN. Mdn) - Anwita Fauziah M; Ridho Mubarak; Wessy Trisna (Universitas Medan Area, 2019)
Minor criminal acts are regulated in Article 352 of the Indonesian Criminal Code, which is a maltreatment that does not cause illness or is prevented from doing office or daily work. Type of normative juridical research. The nature of the research is analytical descriptive is a study that describes, examines, explains and analyzes a legal regulation and describes the results of the data received based on the data source and also by analyzing related cases based on sample cases seen from the Medan District Court Decision in a criminal offense of minor maltreatment . The application of criminal law against criminal offenses of mild persecution in Decision Number: 178 / Pid.B / 2017 / PN Mdn is the perpetrators violating Article 351 paragraph (1) of the Criminal Code, namely: first, legally proven and convincing guilty of committing a criminal offense, secondly, sentenced to prison for 3 (three) months and 15 (fifteen) days, third, stipulates the period of arrest and detention that has been served by the Defendant deducted entirely from the criminal convicted, fourth, orders the Defendant to remain in custody, fifth, imposes case costs to The defendant is Rp. 2,000, - (two thousand rupiah).